A tetratricopeptide repeat domain‐containing protein SSR1 located in mitochondria is involved in root development and auxin polar transport in Arabidopsis. (4th July 2015) - Zhang, Min; Wang, Cuiping; Lin, Qingfang; Liu, Aihua; Wang, Ting; Feng, Xuanjun; Liu, Jie; Han, Huiling; Ma, Yan; Bonea, Diana; Zhao, Rongmin; Hua, Xuejun
Summary Auxin polar transport mediated by a group of Pin‐formed (PIN) transporters plays important roles in plant root development. However, the mechanism underlying the PIN expression and targeting in response to different developmental and environmental stimuli is still not fully understood. Here, we report a previously uncharacterized gene SSR1, which encodes a mitochondrial protein with tetratricopeptide repeat (TPR) domains, and show its function in root development in Arabidopsis thaliana. In ssr1‐2, a SSR1 knock‐out mutant, the primary root growth was dramatically inhibited due to severely impaired cell proliferation and cell elongation. Significantly lowered level of auxin was found in ssr1‐2 roots by auxin measurement and was further supported by reduced expression of DR5‐driven reporter gene. As a result, the maintenance of the root stem cell niche is compromised in ssr1‐2. It is further revealed that the expression level of several PIN proteins, namely, PIN1, PIN2, PIN3, PIN4 and PIN7, were markedly reduced in ssr1‐2 roots. In particular, we showed that the reduced protein level of PIN2 on cell membrane in ssr1‐2 is due to impaired retrograde trafficking, possibly resulting from a defect in retromer sorting system, which destines PIN2 for degradation in vacuoles. In conclusion, our results indicated that SSR1 is functioning in root development in Arabidopsis, possibly by affecting PIN protein expression and subcellular targeting.